A Critical Study on Educational Management Practices in Supporting the Independent Curriculum at the Junior High School Level in Luwuk District, Banggai Regency - Ilham, M. Jayadin; Ahmadin, Ahmadin; Sahi, Yayan; Noprianto, Noprianto (Jambura Journal Civic Education, 2025)
This study aims to critically examine educational management practices in supporting the implementation of the Merdeka Curriculum (Independent Curriculum) at the junior high school level in Luwuk District, Banggai Regency. 21st-century education demands a fundamental transformation in school governance, where educational management must be not only administrative but also transformative. Using a qualitative approach and survey method, this study collected data through open questionnaires, field observations, and in-depth interviews with purposively selected school principals, teachers, and education personnel. The findings reveal that the success of the Merdeka Curriculum implementation is strongly influenced by three key dimensions: visionary and adaptive school leadership, teacher involvement in lesson planning and evaluation, and active community participation in school activities. However, the study also identifies several major challenges, including inadequate teacher training, high administrative burdens, limited digital literacy, lack of learning infrastructure, and weak external partnerships. Overall, this research affirms that the effectiveness of the Merdeka Curriculum is largely determined by the readiness of human resources and the quality of school management. The results of this study are expected to serve as a foundation for formulating contextual, sustainable, and learner-centered management strategies.